The Development of E-Counseling Gestalt Prophetic to Help Students Cope with Academic Procrastination in Indonesian Islamic Higher Education - Rahman, Imas Kania (Islamic Guidance and Counseling Journal, 2020)
The numerous cases of academic procrastination of students in various universities in Indonesia are worrying. In terms of intervention, there is a proven effective approach to improve students’ skill to cope with academic procrastination. It’s called Guidance and Counseling Gestalt Prophetic (G-Pro). Unfortunately, due to a lack of access, G-Pro needs to be developed. This article will present a new approach called E-Counseling Gestalt Prophetic (E-G-Pro). The author used the Borg and Gall model research and development (R & D) model with three research steps: a preliminary study, model development, and model validity. Focus group discussion (FGD) has been done to assess the properness of the model. Four parties, each from information and technology expert, Qur'anic Interpretation expert, Islamic education and religiosity expert, guidance and counselor expert, and counselee, were invited to the FGD. Based on internal judgement by experts and users, the E-G-Pro is highly feasible to be applied to help students cope with academic procrastination in Indonesian Islamic Higher Education.